Cannabidiol as a Promising Strategy to Treat and Prevent Movement Disorders? - Peres, Fernanda F.; Lima, Alvaro C.; Hallak, Jaime E. C.; Crippa, José A.; Silva, Regina H.; Abílio, Vanessa C. (Frontiers in Pharmacology, 2018)
Movement disorders such as Parkinson’s disease and dyskinesia are highly debilitating conditions linked to oxidative stress and neurodegeneration. When available, the pharmacological therapies for these disorders are still mainly symptomatic, do not benefit all patients and induce severe side effects. Cannabidiol is a non-psychotomimetic compound from Cannabis sativa that presents antipsychotic, anxiolytic, anti-inflammatory, and neuroprotective effects. Although the studies that investigate the effects of this compound on movement disorders are surprisingly few, cannabidiol emerges as a promising compound to treat and/or prevent them. Here, we review these clinical and pre-clinical studies and draw attention to the potential of cannabidiol in this field.